Pattern of preoperative uroflowmetry in hypospadias patients and age-matched control patients - Rupesh Sikchi; Arvind Sinha; Manish Pathak; Kirti Kumar J. Rathod; Avinash S Jadhav; Rahul Saxena (Wolters Kluwer Medknow Publications, 2023)
Aim: Patients with hypospadias often present with voiding difficulties after successful repairs. We sought to analyze the degree of uroflowmetric anomalies that may be present in children with hypospadias before a surgical repair. We, thus, undertook this study to compare the pattern of preoperative uroflowmetry study in hypospadias patients and a comparable age-matched control group. Materials and Methods: A total of 90 children underwent preoperative uroflowmetry in the Department of Pediatric Surgery at All India Institute of Medical Sciences (AIIMS), Jodhpur, India, between January 2019 and December 2020. Thirty patients with hypospadias and sixty age-matched controls who presented to the outpatient department without any associated urological or neurological anomalies were included in the study. Uroflowmetry parameters such as maximum urine flow rate (Qmax), average urine flow rate (Qavg), voided volume (VV), urination duration, duration of reaching maximum speed, and urine flow curves of the cases and the control group were measured and compared. Results: The median age of patients at the time of uroflowmetry in the hypospadias group was 7 years, while the same for the control group was 7.5 years. Median maximum urinary flow rates (Qmax) (10.7 vs. 14.45 mL/s, P = 0.01278), average urinary flow rates (Qavg) (6.5 vs. 8.5 mL/s, P = 0.0124), the ratio of maximum urinary flow rates with VV (Qmax/VV) (0.043 vs. 0.053, P = 0.0264) was found to be significant (P < 0.05). These values were significantly lower in the hypospadias group (P < 0.05). The voiding time (43.5 vs. 30 s, P = 0.0285) was significantly higher in the hypospadias group. However, there was no difference in the VV per micturition (219.5 vs. 270.0 mL, P = 0.40) and time to maximum flow rate (10 vs. 10, P = 0.43). Flow curve pattern analysis revealed plateau-shaped curves in 60% of the hypospadias group compared to 27% in the control group, while bell-shaped curve was seen in 37% of the hypospadias group as compared to 65% in the control group which were statistically significant (P = 0.003415). No statistically significant association was found between meatal localization and the uroflowmetry parameters. Conclusion: Children with hypospadias have abnormal uroflowmetry even before surgical correction and have a significantly low maximum urine flow rate. These uroflow anomalies may be due to meatal stenosis or hypoplastic proximal urethra. We postulate that these preoperative abnormal uroflow patterns in patients with hypospadias may contribute to voiding difficulties in repaired hypospadias cases. A greater understanding of the factors behind these uroflowmetric anomalies may allow surgeons to proactively tackle these intraoperatively, leading to better outcomes for patients with hypospadias.